Chiral DNA Nanotubes Self‐Assembled from Building Blocks with Tailorable Curvature and Twist. Issue 49 (26th October 2022) - Dong, Niuniu; Sun, Yishan; Sun, Geng; Zhang, Lei; Sun, Sha
Abstract: DNA nanotubes with prescribed geometry could allow for nanomaterial organization with designed optical or electrical function. As one of the dominating driving forces for DNA nanotube assembly, intrinsic curvature and twist of building blocks can be induced by bending deformation and twisting deformation. However, it is still unknown that how bending and twisting design on nanoscale building blocks affects the geometry of DNA tubes with micrometer length. Here, through targeted base pair deletion or insertion, the amount of bending deformation in building blocks is modulated by length gradient and the amount of twisting deformation is modulated by average twist density. This work systematically explores the independent effect and synergistic effect of two types of deformation on tube geometry, including diameter, chirality, and helical angles, via a streptavidin‐labeling technique. The design rules enable the construction of DNA nanotubes with prescribed chirality and tailored diameters. Abstract : DNA nanotubes with tailorable diameter and chirality are constructed by controlling the curvature and twist in building blocks, which can be generated by bending and twisting deformation. Through targeted base pair deletion or insertion, this work modulates the degree of bending deformation and twisting deformation in building blocks, and explores the geometry of helical tubes via a streptavidin‐labeling technique.